INDONESIA SOFT POWER: TOBA CALDERA AS UNESCO GLOBAL GEOPARK 2020 - Hendra Manurung; Elvinro Sinabariba (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2021)
This research aims to describe analytically Toba Caldera's ability to become one of the UNESCO Global Geopark in 2020. The research used a qualitative research method and is done through literature studies, government documents, and internet sources. Researchers founded, there are inter-linkages amongst Indonesia's central and local government together with stakeholders' continuous contribution who concern with Toba Caldera's sustainable tourism development. Those concerning parties fought for Toba Caldera's recognition status as the UNESCO Global Geopark. From 2011 to 2020, for nine years, the Toba Caldera was finally named a UNESCO Global Geopark during the UN Cultural Body's 209th Plenary Session held in Paris on July 7, 2020. Toba Caldera Geopark was a worldwide tourist magnet as it was home to 13 sites with breathtaking views, namely: Tongging Sipiso-Piso, Silalahi Sabungan, Haranggaol, Sibaganding Parapat, Eden Park, Balige Liong Spige Meat, Situmurun Blok Uluan, Hutaginjang, Muara Sibandang, Sipinsur Bakti Raja, Bakara Tipang, Tele Pangururan, and Pusuk Buhit. A ceremony where the UNESCO Global Geopark placard will be formally given to the Toba caldera is slated to be held in Jeju, South Korea, by September 2020. According to a statement from the Indonesian Embassy in Paris, Toba Caldera is among the 16 new UNESCO Global Geoparks announced by the organization's executive board. North Sumatra provincial administration is hopeful that the recognition will help boost foreign tourist arrivals to the destination. Keywords: Toba caldera, UNESCO, Indonesia soft power, sustainable tourism development, tourist destination